2009
DOI: 10.1589/jpts.21.317
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Community-Based Tai Chi Training on Balance Control during Stair Descent by Older Adults

Abstract: Abstract.[Purpose] The purpose of this study was to investigate the effectiveness of community-based Tai Chi (TC) training on balance control during stair descent by older adults.[Subjects] Participants were randomly assigned to either the TC group or the wellness education (WE) group. The participants in the TC group received TC training three times a week for 12 weeks. The participants in the WE group participated in a health education program for one hour weekly.[Methods] Subjects stood in a predetermined p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 55 publications
4
8
0
Order By: Relevance
“…In the present study, TC training resulted in a 21% increase in the average COP velocity of both limbs during GI and obstacle crossing. This finding agrees with Kim et al 60) who reported a greater COP velocity in older adults during stair negotiation after TC training, as compared to before TC training. The increased COP velocity is likely the result of exercise-induced adaptation of the postural control system during GI or obstacle crossing, and this may be indicative of an improvement in dynamic stability.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, TC training resulted in a 21% increase in the average COP velocity of both limbs during GI and obstacle crossing. This finding agrees with Kim et al 60) who reported a greater COP velocity in older adults during stair negotiation after TC training, as compared to before TC training. The increased COP velocity is likely the result of exercise-induced adaptation of the postural control system during GI or obstacle crossing, and this may be indicative of an improvement in dynamic stability.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study reported that healthy older adults have a greater COP displacement toward the swing limb while performing level walking than those with disability 35) . The findings of our current study agree with the results of the previous studies 50,51) that demonstrated increased displacement of COP in the M-L direction in the performance of obstacle crossing and stair descent after TC training for healthy and fall-prone older adults.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are similar to those reported for level walking, stepping over an obstacle on the ground and descending stairs after TC training 20,50,51) . In those previous studies, Chris et al 20) and Kim 50,51) reported increased posterior displacement of COP after TC training in both healthy and frail older adults when they initiated gait or descended stairs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…TCMBE as an effective, low-cost, and safety exercise approach is widely accepted in elderly people in China and other Asian countries [1214]. During recent years, many studies reported that motor movements of elderly people were improved by participating in Tai Chi, Qigong, and Baduanjin [10, 15, 16].…”
Section: Introductionmentioning
confidence: 99%